(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Objective: to determine the state of the kallikrein-kinin system and protease inhibitors in various clinical forms of glomerulonephritis in children. Materials and methods of the study. To solve the set tasks, 85 children with glomerulonephritis aged 3 to 15 years will be examined. Results and discussion. Patients of the first group showed significant activation of the KKS. The activity of K exceeded the norm by 1.7 times (p<0.001). The level of PC was reduced by 1.1 times (p<0.01). Conclusions: the state of the KKS has certain features in various clinical forms of CGN: mild CGN is characterized by pronounced activation of the KKS controlled by the protease system, probably caused by immune inflammation.